Gallbladder cancer: incidence and pathology: about 175 observations - Estefan, Alberto; Melogno, Silvio; Portos, Roberto (Cirugía del Uruguay, 1973)
Cas':' material includes 175 cases of gall bladder cancer and a aummary of existing literature on the subject. Its incidence and relation with other bilio-hepatic diseases is discussed. Anatomopathological characteristica are discussed. Tumoral diffusion and degree of neoplasic extension at time of diagnosis, is atudied.